Desain Kapal Motor Penyeberangan dengan Sistem Penggerak Hibrida untuk Rute Ujung Surabaya-Kamal Bangkalan - Dwi Agustin; Hesty Anita Kurniawati (Jurnal Teknik ITS, 2017)
The condition of crossing from Ujung to Kamal make loss to PT. ASDP that they plan to close this route. One of the many factors is high operational cost. Besides that, Surabaya is one of the cities in Indonesia with high emission gas. This final project gives solutions to reduce emission gas and reduce the use fossil fuel with hybrid-propulsion concept. The type of hybrid used in this final project are diesel engine, hydrogen fuel cell, and solar panel cell. Payloads of this passenger ship is the amount of passenger crossing from Ujung-Kamal of PT. ASDP. From that data, an initial design is made to determine deck area payload (passenger deck and vehicle deck) so that the main dimension of the vessel is obtained from the decks layout. In continuance, ratio of main dimensions are calculate. There should be a technical calculation concerning on weight, trim, freeboard, and stability. The main dimension calculated are Lpp =42 m; B = 6.9 m; H = 3 m; T = 2 m. The minimum freeboard height is 150 mm, tonnage capacity is 295 GT, and the stability condition of the Passenger Ship has passed the criteria of Intact Stability (IS) Code Reg. III/3.1). The ship building cost is Rp 13,173,344,991.91 with the BEP on the 68th month, so the ship is feasible to be built.